Weed control efficiency and productivity in rice-fish-duck integrated farming system. - Nayak, Prafulla Kumar; Panda, Bipin Bihari; Das, Sunil Kumar; Rao, Koroda rajsekhar; Kumar, Upendra; Kumar, Anjani; Munda, Susmita; Satpathy, Bhavani S.; Nayak, Amaresh K. (Indian Journal of Fisheries, 2020)
Rice farming integrated with fish and ducks potentially provides ecological services and supports effective management of weeds which cause rice yield losses due to growth competitiveness with the available resources and productivity. Present study investigated the efficacy of integrating fish and duck in rice farming for controlling weed infestations and their impacts on productivity and economics of the system. Appraisal on diversity of weeds indicated that grassy weeds (Echinochola colona, Echinochola crusgalli) and sedges (Cyperus difformis, Cyperus iria, Fimbristylis miliacea) were prevalent in rice during tillering stages, while broad leaf (Ludwigia adscendens, Sphenoclea zeylanica) and aquatic weeds (Marsilia quadrifolia, Otellia alismoides, Vallisneria spiralis, Limnophila indica, Ceratophyllum demersum, Hydrilla verticillata) were abundant during active tillering and panicle initiation stages of rice. A significant reduction in weed density and weed biomass was observed in rice-fish (RF), rice-duck (RD) and rice-fish - duck (RFD) integration. However, weed control efficiency (WCE %) was significantly (p<0.05) higher in RFD. The weed biodiversity in terms of species richness (Simpson’s index) and species diversity (Shannon-Wiener index) decreased significantly, while Pielou evenness community index increased in RFD, signifying weed community composition was highly diversified with reduction of formerly dominant weed species. Rice agronomic characteristics, productivity and economic returns were higher in integrated system indicating over all improvements in ecology and productivity. Better growth of fishes accrued with RFD integrated system, possibly, due to the better nutrient availability. Thus, fish and duck can be used as bio-control agents for weed management in rice farming for enhancing productivity in areas where application of chemical herbicides may be partially or totally eliminated in transplanted lowland system. Keywords: Bio control of rice weeds, Rice-fish-duck integrated farming system, Weed biodiversity, Weed control efficiency